Seismic Response and Vibration Reduction Analysis of Suspended Structure under Wave Passage Excitation - Wenhua Cai; Bujun Yu; Fajong Wu; Jianhua Shao (Advances in Civil Engineering)
In order to study the influence of traveling wave effect on the seismic response and damping effect of suspended structure, a series of shaking table tests of the 1 : 20 suspended structure have been carried out to compare and analyze the dynamic responses of suspended structures under two points and a consistent input. The vibration damping effect and vibration reduction law of suspended structure are discussed at different apparent wave velocity and in the different connection. The research shows that the damping suspended structure has a good damping effect, and the amplitude reduction of the top displacement peak response is up to 15%, which corresponds to smaller apparent velocities. Moreover, the upper bound of the maximum acceleration response at the structures’ top under nonuniform input motions equals that of the uniform motion. However, there is a hysteresis in the acceleration response under wave travelling excitations, and the smaller the apparent wave velocity, the more obvious the hysteresis.